Legal Normative Analysis of Social Duty Of Hospital As Reviewed From Law Number 17 Of Year 2023 Concerning Health By Regional Public Hospital (Case Study Sultan Syarif Mohammad Al Kadri Pontianak Regional General Hospital) - Josepb Nugroho Halomoan Simarmata; Siti Nurhayati; Bambang Fitrianto (International Journal of Society and Law, 2025)
Hospital is the most important part of providing specialized healthcare service tocitizen in Indonesia. But there is concern about the healthcare that is provided at hospitals became profit oriented rather than social purpose. Every legal product about hospitals always mentions about the social function of hospitals. As time flies, the health law in Indonesia that is dynamic already changes, is the Law that rules about hospital social function still relevant?. The method used in this research is normative juridical research by reviewing the obligation to do hospital social function and social-spirited function by the regency general hospital such is implementing Regional Public Service Agency financial management pattern with the legislative approach. The result is hospital social function that is mentioned in Law number 17 of Year 2023 concerning Health is using the exact word that was mentioned in Law produced fourteen years ago. So this Law seems ineffective as there are so many changes in Legal Health reality as long as that period of time. The conclusion is there was a lack of caution in the processes of Legal Product Production as cause if the problem, so a change in regulation of hospital social function is needed to make sure it is relevant to date.